Problems with Paranthropus. (20th March 2023) - Sponheimer, Matt; Daegling, David J.; Ungar, Peter S.; Bobe, René; Paine, Oliver C.C.
Abstract: Carbon isotopic analysis has been challenging our ideas about hominin diet for nearly 30 years. The first study in 1994 revealed that Paranthropus robustus from South Africa consumed principally C3 foods (e.g., tree fruits and leaves) but also about 25% C4 /CAM resources (e.g., tropical grasses and sedges). This result was largely consistent with morphological and dental microwear evidence suggesting P. robustus had a diet which included hard objects like nuts and seeds. Decades later, however, P. boisei from eastern Africa was shown to have eaten nearly 80% C4 /CAM plants like the contemporaneous grass-eating primate Theropithecus . Moreover, dental microwear revealed no evidence of hard object consumption in P. boisei, suggesting a diet of tough foods such as grass or sedge leaf and stem. So Paranthropus presents us with two central problems: 1) Why do dietary proxies suggest different diets for the two robust australopiths despite their morphological congruity; and 2) How could P. boisei have consumed tough foods with teeth that seem unsuited to the task. Here we review these questions and more with a particular focus on new isotopic data from the Omo and insights that can be gleaned from mammals outside the haplorrhine primates. We argue that extant Primates do not capture the ecomorphological diversity of P. boisei and other extinct primates and should not narrowly circumscribe the behaviors we ascribe to extinct taxa. We also discuss possible digestive strategies for P. boisei in light of its morphology, dietary proxy data, food mechanical properties, and comparative data on mammalian digestive kinetics.